Thermal-hydraulic characteristics of nitric acid: An experimental and numerical analysis - Alali, Sabah A. (2024)
Nitric acid is one of the most important products in the chemical industry, ranking third globally in terms of acid production. Although nitric acid has many industrial applications, its primary function is the production of ammonium nitrate, which is used in the fertilizer industry. In this report, we propose a plan for an Ostwald process plant that will produce 1000 metric tons of nitric acid per day. Based on an effective energy analysis, we have concluded that using a single pressure method provides optimal results. First, ammonia is vaporized using process heat at 1000 kPa and 35 °C before being superheated using steam to a temperature of 80 °C. Filtered air is compressed by an axial compressor to a discharge pressure of approximately 740 kPa and a temperature of 155 °C. After conducting a site evaluation, three existing manufacturing sites are being considered for the acid production plant: Ogun State (Nigeria), Gwadar Seaport (Pakistan), and Ras-Alkhair Seaport (Saudi Arabia). Based on the results of the site assessment, Ras-Alkhair has been selected as the most suitable location for the nitric acid plant. About 65 % of all nitric acid produced worldwide is used in the production of ammonium nitrate, which is in turn used in the fertilizer and explosives industries. The synthetic nitric acid that will be produced from this plant will be used in the production of fertilizers.